2018
DOI: 10.2478/rjim-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and prognostic value of serum endocan in patients with cirrhotic cardiomyopathy

Abstract: Endocan is a promising biomarker of severity of cirrhosis and may help in the diagnosis of cardiac dysfunction in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(29 reference statements)
0
7
0
1
Order By: Relevance
“…Also, there are reports that observed decreased Endocan levels in adult NAFLD [ 27 ]. Decreased Endocan levels were also associated with cardiac complications in adult cirrhotic patients [ 28 ]. All these previous data suggest that a decrease in Endocan levels could be linked with an increase in cardiac complications in chronic hepatic diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Also, there are reports that observed decreased Endocan levels in adult NAFLD [ 27 ]. Decreased Endocan levels were also associated with cardiac complications in adult cirrhotic patients [ 28 ]. All these previous data suggest that a decrease in Endocan levels could be linked with an increase in cardiac complications in chronic hepatic diseases.…”
Section: Resultsmentioning
confidence: 99%
“…In non-dialysis chronic kidney disease patients (stage 5), circadian heart rate variability correlates positively with serum ESM1 concentration [ 27 ]. Toshikuni et al showed that liver cirrhosis patients have high levels of serum ESM1 and that this protein may be a survival marker of liver cirrhosis [ 28 ] and cirrhotic cardiomyopathy [ 29 ]. ESM1 overexpression was reported to increase the expression of tumor necrosis factor-α (TNF-α) and monocyte chemotactic protein-1, which are involved in liver inflammation and fibrosis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These patients already face a challenging transplantation journey from a significant pretransplant disease burden [50]. Unsurprisingly, a significant number of cardiac complications has been observed in transplant patients, with the most common being refractory hypotension [51]. The current literature suggests that transesophageal echocardiography should be done immediately post-transplant as standard of care, because it provides invaluable information relevant to the required level of post-transplant cardiac support [46] (see Figure 4).…”
Section: Liver Transplantationmentioning
confidence: 99%